Three‐year follow up of adrenal incidentalomas in a New Zealand centre. Issue 3 (5th March 2020) - Goh, Ziwei; Phillips, Ian; Hunt, Penny J.; Soule, Steven; Cawood, Tom J.
Abstract: Background: The international guidelines for management of adrenal incidentalomas (AI) are becoming more conservative. These changes are based on the growing body of evidence suggesting that non‐functioning adenomas have a low likelihood of becoming functional or malignant over time. Aims: To follow up at least 100 patients for 3 years who were originally found to have benign adrenal adenomas which were non‐functional or had subclinical Cushing syndrome (SCS). Methods: This study prospectively evaluated consecutive patients aged 18 years or older with benign adrenal incidentalomas (AI), not treated with adrenalectomy, which were non‐functioning or had SCS. The initial and follow‐up evaluation, including clinical assessment, hormonal investigations and imaging were coordinated via a standardised nurse‐led AI clinic. Results: Of 233 patients referred to the AI clinic, 101 patients met the inclusion criteria and completed 3‐year follow up. Most of those excluded were due to incomplete initial or follow‐up evaluation or were not true AI. Most AI either remained stable or decreased in size on repeat imaging, while 5% of patients had AI enlargement of >5 mm diameter. No patient developed features suggesting adrenal carcinoma. Ninety‐two patients had an initial diagnosis of non‐functioning adenoma and nine patients had SCS. After 3 years (range 2.9–4.7 years), five of the nine patients with SCS showed normalisation of cortisol parameters (44%), and five of the 92 non‐functional AI patients developed SCS (5%). Conclusion: After 3 years of follow up, approximately half of patients with SCS normalised, while 5% of patients with initially non‐functioning adenomas developed biochemical evidence of SCS. This study found a low likelihood of progressive hormonal excess with no evidence of malignancy developing on follow‐up evaluation, providing support for the shift towards the more conservative approach to management of AI recommended in recent guidelines.